Study on Damage Index for Beam–Column Joints with Flush End-Plate Connections - Jizhi Su; Jinpu Zhou; Weiran Liu; Yong Li; Haifeng Yu; Qilian Li (Buildings)
Experimental results from 109 flush end-plate (FEP) connections were analyzed to investigate the failure modes and damage index of FEP connections across various damage states. The present study was conducted in accordance with the performance design objectives specified in China’s GB50011-2010 Code for Seismic Design of Buildings. The observed rotation angles and corresponding rotation factors were systematically categorized using a probabilistic statistical approach, with the 95% confidence lower limit as the primary constraint. The damage states of FEP connections were classified as virtually undamaged, lightly damaged, moderately damaged, severely damaged, and joint failure. A minimum plate thickness of 12 mm and a minimum high-strength bolt diameter of 20 mm are recommended to be used for the FEP connections, in accordance with building codes in China, the United States, and Europe. Quasi-static tests of six FEP connections were conducted to validate the damage-state categorization. The results revealed that for connections undergoing moderate and severe damage, the mean rotation factor deviated from the theoretical values proposed in this study by 3.7% and 9.4%, respectively. Therefore, the damage state of FEP connections can be reliably predicted based on different rotation angles using the damage-state categorization presented herein.